Endothelial Wound Repair of the Organ-Cultured Porcine Corneas. (3rd July 2018) - Smeringaiova, Ingrida; Reinstein Merjava, Stanislava; Stranak, Zbynek; Studeny, Pavel; Bednar, Jan; Jirsova, Katerina
ABSTRACT: Purpose : To assess whether injured porcine endothelium of small and large corneoscleral disc differ in its reparative/regenerative capacity under various conditions of organ culture storage. Material and methods : 166 paired porcine corneas were trephined to obtain tissues with diameter 12.0 mm and 17.5 mm (with area neighboring endothelial periphery). In tested discs, central endothelium was mechanically wounded. Density of live endothelial cells (LECD), percentage of dead cells (%DC), coefficient of variation and cell hexagonality were assessed in central and paracentral endothelium following 5- or 9-day incubation in medium with 2% or 10% fetal bovine serum. The parameters were assessed also in fresh and intact cultured discs. Dead endothelial cells (EC) were visualized by trypan blue, cell borders by Alizarin Red S dye. Endothelial imprints were immunoassayed for the proliferation marker Ki-67 and the nucleolar marker fibrillarin. Results : In fresh corneas, the LECD/mm 2 (mean ± standard deviation) were 3998.0 ± 215.4 (central area) and 3888.2 ± 363.1 (paracentral area). Only the length of storage had significant effect on wound repair. Lesion was repaired partially after 5-day and fully after 9-day cultivation. After 9-day storage in medium with 10% serum, the mean LECD detected in small discs were 2409.4 ± 881.8 (central area) and 3949.5 ± 275.5 (paracentral area) and in large discs the mean LECD were 2555.0 ± 347.0 (central area) and 4007.5 ± 261.2 (paracentral area). Ki-67 showed cell proliferation associated with healing of EC of both large and small corneas. Conclusions : The lesions were completely repaired within 9 days of storage. Presence of the area, where stem cells appear to be located, contributes to stimulation of endothelial reparation less than serum concentration and time of culture. Both cell migration and proliferation contribute to the wound repair.